Characteristic Lightlike Submanifolds of an Indefinite S-Manifold - Jae Won Lee (International Journal of Mathematics and Mathematical Sciences)
We study characteristic r-lightlike submanifolds M tangent to the characteristic vector fields in an indefinite metric S-manifold, and we also discuss the existence of characteristic lightlike submanifolds of an indefinite S-space form under suitable hypotheses: (1) M is totally umbilical or (2) its screen distribution S(TM) is totally umbilical in M.